2010
DOI: 10.1007/s00280-010-1439-1
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 receptor antagonist attenuates cyclophosphamide-induced mucositis in a murine model

Abstract: The pretreatment with rhIL-1Ra effectively protected murine gastrointestinal system from clinically relevant cyclophosphamide regimens. The identification of these protective effects of rhIL-1Ra highlights clinical values of this protein for the prevention of CIM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Newer studies have continued to investigate the potential for use of anti-inflammatory agents for mucositis management in preclinical models, although focused on broader outcome measures to link effectiveness with mechanisms. Since the last pathogenesis update, there have been two preclinical studies testing IL-1ra, the naturally occurring IL-1 antagonist [47][48][49]. Both studies found protection against chemotherapy-induced intestinal mucositis and crypt destruction in the small intestine which was attributed to apoptosis prevention.…”
Section: Sophisticated Targeting Of Inflammationmentioning
confidence: 99%
“…Newer studies have continued to investigate the potential for use of anti-inflammatory agents for mucositis management in preclinical models, although focused on broader outcome measures to link effectiveness with mechanisms. Since the last pathogenesis update, there have been two preclinical studies testing IL-1ra, the naturally occurring IL-1 antagonist [47][48][49]. Both studies found protection against chemotherapy-induced intestinal mucositis and crypt destruction in the small intestine which was attributed to apoptosis prevention.…”
Section: Sophisticated Targeting Of Inflammationmentioning
confidence: 99%
“…, 5‐FU) and ‐independent ( e.g. , cyclophosphamide) chemotherapy drugs (4, 9, 28). Our results also corroborate recent findings that the induction of HS/PC quiescence before chemotherapy promotes hematopoietic recovery and improves animal survival in lethal‐dose chemotherapy (2931).…”
Section: Discussionmentioning
confidence: 99%
“…One good example that can be easily produced and purified in E. coli is recombinant human interleukin-1 receptor antagonist (rhIL-1Ra) 7 . rhIL-1Ra can be produced by E. coli at large scale in soluble form.…”
Section: The Purpose Of Target Protein Determines Its Formmentioning
confidence: 99%
“…A good example of how to express and purify soluble rhIL-1Ra is indicated below. 18 The interleukin-1 receptor antagonist (IL-1Ra) is a protein encoded by the IL1RN gene. IL1Ra was initially called the IL-1 inhibitor and was discovered in 1984.…”
Section: The Purification Of Soluble Recombinant Proteinmentioning
confidence: 99%